1997
DOI: 10.1111/j.1439-037x.1997.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Drought Resistance in Spring Chickpea in the Mediterranean Region*

Abstract: Even though chickpea {Cicer arietinum L.) is well adapted to growing on stored soil moisture in drought-prone environments, drought is a major yield reducer in most chickpea-growing regions. Little progress has been made in breeding for improved performance under drought stress for want of a reliable and repeatable method of screening for drought resistance. Therefore, a study was initiated in 1990 to develop a screening technique and a rating scale to evaluate germplasm for drought resistance. A spring date-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…The results of Nayyar et al (2006) revealed that 14 days water stress, to kabuli type chickpea exhibited 80% reduction in yield as compared with 64% reduction observed in desi chickpea and also noted that decrease in water leave potential was faster in kabuli as compared to desi. Singh et al (1997) also confirmed that desi chickpea produces higher pods and yield than kabuli type. The chickpea lines with higher plant water status and high leaf water potential (LWP) produce higher number of seed per plant, seed/pod, harvest index and grain yield (Yadav et al, 2005).…”
Section: Grain Yieldsupporting
confidence: 69%
See 1 more Smart Citation
“…The results of Nayyar et al (2006) revealed that 14 days water stress, to kabuli type chickpea exhibited 80% reduction in yield as compared with 64% reduction observed in desi chickpea and also noted that decrease in water leave potential was faster in kabuli as compared to desi. Singh et al (1997) also confirmed that desi chickpea produces higher pods and yield than kabuli type. The chickpea lines with higher plant water status and high leaf water potential (LWP) produce higher number of seed per plant, seed/pod, harvest index and grain yield (Yadav et al, 2005).…”
Section: Grain Yieldsupporting
confidence: 69%
“…High temperature stress also causes yield losses because of damage to reproductive organs (Anyia and Herzy, 2000) and had reduced total dry matter and grain yield during drought (Leport et al, 2006). Singh et al (1997), Kashiwagi et al (2005) and Lopez et al (2006) have screened out some pulses germ plasm accessions with greater genetic variability in various traits. They also identified some drought tolerant related characteristics in the chickpea plant.…”
Section: Introductionmentioning
confidence: 99%
“…Some losses are due to intermittent drought during the vegetative phase while others are due to terminal drought during reproductive development Singh et al, 1997a;Serraj et al, 2004b). The severity of drought stress is unpredictable as it depends on many factors such as occurrence and distribution of rainfall, evaporative demands of the atmosphere and moisture storing capacity of the soils (Wery et al, 1994).…”
Section: Drought Stressmentioning
confidence: 99%
“…Moinuddin and Chopra (2004) suggested that cultivars with high osmotic adjustment (OA) generally showed improved plant water potential and proved significantly superior to one with low OA with respect to grain yield and other parameters. Early plant vigour and fast ground cover are the yield enhancing traits under drought in chickpea (Singh et al, 1997). Shoot and root traits play an important role in regulating water use by crop plant (Subbaroa et al, 1995).…”
Section: Plant Characteristicsmentioning
confidence: 99%